Prognostic Significance of New AJCC Tumor Stage in Patients with Pancreatic Ductal Adenocarcinoma Treated with Neoadjuvant Therapy - Chatterjee, Deyali (Am J Surg Pathol, 2017)
The American Joint Committee for Cancer (AJCC) has adopted a size-based T stage system (8(th) edition) for pancreatic ductal adenocarcinoma (PDAC), defined as follows: pT1 ≤ 2 cm (pT1a ≤ 0.5 cm, pT1b > 0.5 cm and < 1 cm, and pT1c 1–2 cm); pT2 > 2 cm and ≤ 4 cm; and pT3 > 4 cm. However, the prognostic value of this new T staging system has not been validated in patients who underwent pancreaticoduodenectomy (PD) after neoadjuvant therapy. In this study, we analyzed 398 PDAC patients who underwent neoadjuvant therapy and PD at our institution from 1999 to 2012. The results were correlated with clinicopathologic parameters and survival. The new T stage correlated with lymph nodes metastasis (p<0.001), tumor regression grade (p<0.001), disease-free survival (DFS, p<0.001) and overall survival (OS, p<0.001). None of the patients with ypT0 had recurrence or died of disease. Among the patients with ypT1 disease, patients with ypT1a and ypT1b had better DFS (p=0.046) and OS (p=0.03) than those with ypT1c. However, there was no significant difference in either DFS or OS between ypT1c and ypT2 or between ypT2 and ypT3 groups (p>0.05). In multivariate analysis, new ypT3 stage was associated with shorter OS (p=0.04), but not DFS (p=0.16). Our results show that the new ypT stage better stratify survival than the ypT stage in AJCC 7(th) edition for PDAC patients who received PD after neoadjuvant therapy, and that tumor size cut off of 1.0 cm work better for ypT2 than the proposed tumor size cut off of 2.0 cm in this group of patients.